Pathogenicity Characteristics of Front, Middle, and Hind Nipah Worm (Namalycastis rhodochorde) Digestive Tract Bacteria - Indrawati, Dian; Yanti, Ari Hepi; Kurniatuhadi, Rikhsan (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Nipah worms (Namalycastis rhodochorde) are one of Indonesia's invertebrate species used as high-protein aquaculture feed. The presence of pathogenic bacteria is a factor in the decline in quality and quantity in nipah worm cultivation, especially bacteria originating from the digestive tract of nipah worms. This study was conducted to examine the characteristics of pathogenicity of bacteria originating from the digestive tract of Nipah worms in the form of hemolysis and DNase activity. The hemolysis and DNase activity tests were performed using the streak plate method on Blood Agar Plate (BAP) and DNase Agar media. The results obtained in the hemolysis test showed a positive reaction in 68 isolates (90.7%), consisting of 5 α-hemolysis isolates, 63 β-hemolysis isolates, and 7 γ-hemolysis isolates. β hemolysis or complete hemolysis was found in 27 isolates in the foregut, 18 isolates in the midgut, and 18 isolates in the hindgut. The results obtained in the DNase activity test were positive in 17 isolates (22.7%), consisting of 9 isolates from the front digestive tract, 1 isolate from the middle digestive tract, and 7 isolates from the rear digestive tract. This study concludes that the high levels of hemolysis and DNase activity in bacterial isolates from the digestive tract of the nipah worm are predictors of pathogenicity. Bacterial isolates from the foregut showed the highest pathogenic activity, which is thought to be due to the presence of bacteria carried during the feeding process of the nipah worm.